Platelet Preservation. III. The Influence of Dimethylsulfoxide and Cooling Conditions on Serotonin Uptake Velocity and Response to Hypotonic Stress of Human Platelets - Odink, J; Sprokholt, R (Thrombosis and Haemostasis, 1976)
1. Serotonin uptake velocity of human platelets was found to be reversibly inhibited by the presence of dimethylsulfoxide (DMSO).2. Incubation of platelet concentrates in the presence of DMSO for 90 minutes at room temperature decreased serotonin uptake velocity and response to hypotonic stress.3. The serotonin uptake velocity was not substantially influenced by the temperature of incubation with DMSO.4. The best recovery of serotonin uptake velocity after cryopreservation in the presence of DMSO was observed when DMSO was added quickly before cooling and removed quickly after thawing.5. No significant differences were observed in serotonin uptake velocity and response to hypotonic stress after cryopreservation in the presence of DMSO when cooling rates were varied from 2 to 10° C/min.